Heat Stress Altered the Vaginal Microbiome and Metabolome in Rabbits - Shi, Yu; Tang, Lipeng; Bai, Xue; Du, Kun; Wang, Haoding; Jia, Xianbo; Lai, Songjia (Frontiers in Microbiology, 2022)
Heat stress adversely affect the growth, maturation parental gametes and reproduction functions. However, the influences of heat stress on the internal environment of vagina have not been well elucidated. In the study, the effects of heat stress on both vaginal microbiota and metabolites were described. Heat stress altered the relative abundance of the predominant microbiota and significantly decreased the abundance of Lactobacillus in vagina, which was reported as the dominant genus in human vagina and beneficial for health. Moreover, as many as 158 metabolites increased or decreased significantly in rabbit vagina after heat stress exposure. Among them, the endocrine hormone estradiol (E2) increased and positively associated several metabolites, such as linolelaidic acid (C18:2N6T) and syringic acid. Further, most of the differential metabolites were enriched in vitamin digestion and absorption, steroid biosynthesis, endocrine and other factor-regulated calcium reabsorption and biosynthesis of unsaturated fatty acid pathways, reflecting heat stress affected the calcium metabolism, vitamin endocrine system and hormone regulation of vaginal ecology. These findings might help understand the regulation mechanism of vagina system under heat stress and display a prospective of factor that heat stress affect the reproductive function of female animals.